1994
DOI: 10.1002/pi.1994.210350210
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the chemical interactions that occur on polyaniline with inverse thin layer chromatography

Abstract: Inverse thin layer chromatography is used to characterise the chemical interactions that occur on polyaniline that has been electrochemically deposited on to a support. Amino acids are used as the molecular probe species by which the retention behaviour can be related to particular chemical interactions. The mobile phase is also varied, with respect to its polarity and pH, in order to add a further dimension to the qualitative information that is obtained. Anion exchange interactions are found to be the domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This type of study helps to explain the affinity differences found in the whisky experiment mentioned above. Several studies indicate there is an effect of pH on the properties and structure of PANI. PANI-EB and -ES are very sensitive to environments with different pH values; this produces changes in the backbone of both PANI forms due to protonation and deprotonation of the imine nitrogen of the quinoid segment . The pH of whisky is 4.43, and when PANI-EB (Figure a) was mixed with whisky, its pH was increased to 4.94, which suggests that the imine nitrogens were partially protonated (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of study helps to explain the affinity differences found in the whisky experiment mentioned above. Several studies indicate there is an effect of pH on the properties and structure of PANI. PANI-EB and -ES are very sensitive to environments with different pH values; this produces changes in the backbone of both PANI forms due to protonation and deprotonation of the imine nitrogen of the quinoid segment . The pH of whisky is 4.43, and when PANI-EB (Figure a) was mixed with whisky, its pH was increased to 4.94, which suggests that the imine nitrogens were partially protonated (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…49−51 PANI-EB and -ES are very sensitive to environments with different pH values; this produces changes in the backbone of both PANI forms due to protonation and deprotonation of the imine nitrogen of the quinoid segment. 52 The pH of whisky is 4.43, and when PANI-EB (Figure 10a) was mixed with whisky, its pH was increased to 4.94, which suggests that the imine nitrogens were partially protonated (Figure 10b). On the other hand, when PANI-ES (Figure 10a) was mixed with whisky, the pH of the solution was decreased to 3.75, which suggests that the imine nitrogens of PANI-ES were partially deprotonated (Figure 10b) when it was subjected to a low pH environment.…”
Section: Affinity Of Polyaniline-based Materials Toward Tcamentioning
confidence: 99%
“…Each chain was separated by a distance of at least 5 Å, to give PANI‐EB and PANI‐ES spherical nanoparticles of 90 Å diameter. The emeraldine forms (base and salt) of PANI are sensitive to pH change (Lindfors and Ivaska , Patil et al , Tanwar and Ho ), which produces changes in the backbone because of the imine nitrogen located in the quinoid segment (INQS) undergoing protonation or deprotonation (Teasdale and Wallace ). Therefore, three different PANI‐EB nanoparticles were built in order to simulate the environments in methanol solution (0% protonated INQS), whisky (50% protonated INQS) and red wine (75% protonated INQS).…”
Section: Methodsmentioning
confidence: 99%